2019
DOI: 10.17221/93/2019-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Risk aversion level influence on farmer's decision to participate in crop insurance: A review

Abstract: Agricultural insurance in Indonesia is focused specifically on rice farming and is locally known as Asuransi Usahatani Padi (AUTP). To encourage farmer participation, the government subsidises farmers’ cost of insurance (premium) by 80%. Despite high subsidy, AUTP is still unable to reach the coverage target. The objectives of this study are to investigate farmers’ Risk Aversion Level (RAL), its influence on farmers’ decision to participate in AUTP, and the effect of farmers’ participation in AUTP on their inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 14 publications
1
20
1
Order By: Relevance
“…This ambiguity has been discussed by Peng and Pang (2019), who found that farmers' risk aversion increased with the farm size. In contrast with our research finding, Lyu and Barré (2017); Belissa et al (2019) and Yanuarti et al (2019) have found that farmer's risk aversion level had a significant influence towards their decision to participate in insurance. Farmers with high risk aversion would be willing to join agricultural insurance.…”
Section: Resultscontrasting
confidence: 99%
“…This ambiguity has been discussed by Peng and Pang (2019), who found that farmers' risk aversion increased with the farm size. In contrast with our research finding, Lyu and Barré (2017); Belissa et al (2019) and Yanuarti et al (2019) have found that farmer's risk aversion level had a significant influence towards their decision to participate in insurance. Farmers with high risk aversion would be willing to join agricultural insurance.…”
Section: Resultscontrasting
confidence: 99%
“…The impact of AISP on farmers’ income is mainly manifested in reducing income fluctuation. Research shows that the agricultural production income of subsidized farmers is more stable after purchasing insurance [ 2 , 3 ]. Agricultural insurance can play a role in hedging risks when the grain yield or the price of grain falls [ 4 ] and compensate farmers for losses through a compensation mechanism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Farmers well receive this program because it helps them provide farming capital for the next planting season when they experience failure in farming [26]. However, farmer participation in this program is low, even though the government subsidized the premium by 80% [27]. It shows that a more comprehensive policy framework and a careful implementation of that policy are required to mitigate the impact of climate change on rice farming in Indonesia.…”
Section: Overview Of Indonesian Rice Farmingmentioning
confidence: 99%